The Marxan model for determining no-catch zones based on conservation targets in the north-eastern region of Simeulue District. Issue 1 (March 2021) - Aulia, F; Rusdi, M; Deli, A; Fuadi, A; Irham, M; Indra, I
Abstract: Aceh Governor's Decree Number 523/1297/2018 concerning the Determination of Reserve Reservation for Aceh Waters allows Pinang, Siumat and Simanaha Islands (PISISI) in the northeast region of Simeulue Island to become one of the conservation zones that have a no-take zone. Therefore, it is necessary to have a scientific analysis of the management and zoning plan especially in determining the location of the core zone (no-take zone). Determination of the core zone is the most important part in planning to protect coastal areas as a form of sustainable management of fish resources and the environment. The purpose of this study is to determine the location of no-take zones based on conservation targets that have high biodiversity values in the PISISI area of Simeulue Island. Therefore, the Marxan model is used which is a design plan for the conservation zoning design. The analysis shows that there are eight areas that can be used as a no-catch area based on coastal habitats, biodiversity, and high conservation value. The model results indicate that no-take zones will be able to protect 80% of conservation targets. Simulation results also show that the area of the no-take zone is around 2, 283.89 ha.